2007
DOI: 10.1007/s11199-007-9319-9
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Power of Feminism: Is Feminism Good for Romantic Relationships?

Abstract: Past research suggests that women and men alike perceive feminism and romance to be in conflict (Rudman and Fairchild, Psychol Women Q, 31:125-136, 2007). A survey of US undergraduates (N=242) and an online survey of older US adults (N=289) examined the accuracy of this perception. Using self-reported feminism and perceived partners' feminism as predictors of relationship health, results revealed that having a feminist partner was linked to healthier relationships for women. Additionally, men with feminist pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…This implies that the improved social status of women in society does not seem to come at the cost of men's subjective well-being. This finding is broadly consistent with the results of a study conducted by Rudman and Phelan (2007) in which men who were dating feminists reported increased relationship stability and sexual satisfaction as compared to men who were dating more traditional women.…”
Section: Discussionsupporting
confidence: 89%
“…This implies that the improved social status of women in society does not seem to come at the cost of men's subjective well-being. This finding is broadly consistent with the results of a study conducted by Rudman and Phelan (2007) in which men who were dating feminists reported increased relationship stability and sexual satisfaction as compared to men who were dating more traditional women.…”
Section: Discussionsupporting
confidence: 89%
“…For example, at the individual level of analysis, holding strong feminist beliefs has been linked with high self-esteem (Fischer and Good 1994), self-efficacy (Eisele and Stake 2008), academic achievement (Valenzuela 1993), rejection of feminine norms for thinness and appearance (Hurt et al 2007), sexual well-being (Schick et al 2008), and sexual openness (Bay-Cheng and Zucker 2007). At the level of interpersonal relationships, although some women continue to equate feminism with heterosexual disharmony (Rudman and Fairchild 2007), this stereotype is debunked by survey findings from men with feminist women partners who rate their relationship as both stable and sexually satisfying (Rudman and Phelan 2007). As for being nonfeminist, endorsement of passive acceptance was related to college women's low expectations for having an egalitarian intimate relationship as well as depressed sexual assertiveness (Yoder et al 2007b).…”
Section: Feminist Beliefsmentioning
confidence: 99%
“…For example, men as well as women have differing attitudes regarding feminism and changing gender roles in society. Rudman and her colleagues [20,21] considered the perception that feminism and romance are in conflict. Believing that feminism and equal rights conflicted with heterosexual romance and sexual relationships was negatively related to feminist attitudes for both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Applying Rudman's [20,21] research to these gender measures would suggest that those who are more traditional in terms of gender roles would also be more traditional in their attitudes towards indicators of commitment such as engagement rings and weddings.…”
Section: Introductionmentioning
confidence: 99%